Bibliometric and visualized analysis of current advances and future directions in epilepsy: from molecular basis to therapy - Du, Chengqiang; Xu, Xinlei; Lv, Yehui; Tong, Fang; Lin, Ruofan; Yang, Zhifang (Frontiers in Neurology, 2025)
PurposeThrough a visual analysis of the literature on epilepsy research in the Web of Science Core Collection, this study aims to explore the molecular basis, providing a reference for scholars and professionals in related fields.MethodsThe search formula is generated using the Mesh keyword list in PubMed. Subsequently, English-language literature is retrieved from the Web of Science Core Collection, with the search period set from January 1, 2015, to December 31, 2024. The study calculates the annual number of publications and citations and analyzes the trends. CiteSpace 6.2. R4 software is used to perform a visual analysis of the retrieved documents.ResultsThe search retrieved 1,485 articles related to molecular basis of epilepsy research, with an average annual growth rate of 14.41%. Based on the publication trend line for this period, it is predicted that approximately 208 articles will be published in this field in 2025.ConclusionThis study examines the dynamic evolution of epilepsy from molecular mechanisms to clinical treatment. Ion channel abnormalities (e.g., KCNQ2 and SCN1A mutations) and neuroinflammatory pathways have become central to basic research, guiding targeted drug design. However, gaps remain between basic research and clinical application, as discoveries like circRNA regulation and glial-neuron interactions have not yet led to effective therapies, and emerging technologies such as optogenetics and nano-drug delivery systems still require clinical validation.